Relation between maximal anaerobic power output and tests on rowing ergometer - Šmída, M.; Clementis, M.; Hamar, D.; Macejková, Y. (Acta Facultatis Educationis Physicae Universitatis Comenianae, 2017)
Aim of this study was to compare relation between maximal anaerobic power output and 2,000 m test on rowing ergometer and relation between 6,000 m test and 2,000 m on rowing ergometer. It can be assumed that 2,000 m performance on rowing ergometer will significantly correlate with maximal anaerobic power output and 6,000 m performance. A group of 9 welltrained rowers (age: 18.3 years ± 2.8 years, sport age: 4.9 years ± 3.7 years, weight: 78.9 kg ± 12.2 kg, height: 182.3 cm ± 7.6 cm) performed three tests in 1 week to determine maximal anaerobic power, 6,000 m and 2,000 m performance on Concept 2 model D rowing ergometer. A value of simple maximal stroke out of 10-second all-out test with drag factor set to 200 was taken as a measure of maximal anaerobic power. Drag factor for 6,000 m and 2,000 m test was set individually. Average power during these tests was record. Research showed that both maximal anaerobic power and 6,000 m test correlated with 2,000 m test on rowing ergometer significantly (rmap = 0.93 p < 0.01, r6k = 0.95 p < 0.01). Maximal anaerobic power and 6,000 m tests seem to be good predictors for 2,000 m score on rowing ergometer. However, maximal anaerobic power test can be used to monitor rowing performance during specific training cycle instead of longer and more demanding 6,000 m test.